Trade facilitation in times of pandemic: Practices from North and Central Asia - Yelena Vassilevskaya (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2020)
The COVID-19 pandemic and associated attempts to contain its spread have created unprecedented hurdles to international trade. This paper reviews trade facilitation measures implemented in North and Central Asia (NCA), including transport and trade finance facilitation. All NCA countries have sought to protect the public health by restricting movement of people (including across borders) and applying special sanitary regulations at border crossings. These have included requirements to sanitize trucks, protect customs officials, change drivers, and requiring COVID-19 tests from drivers. Such requirements continue to create significant logistical issues, with often insufficient facilities for drivers. Sanitary requirements have proved simpler to implement for rail freight, creating an advantage for countries with well-developed rail networks. A number of common patterns emerge from the efforts of NCA countries to facilitate trade and transit. First, all governments have formed intragovernmental bodies to coordinate their COVID-19 responses. However, these bodies often lack the competency, mandate or reach to implement effective trade facilitation measures. Second, countries have simplified customs procedures for essential goods, typically food and medical supplies. Some countries initially implemented restrictions on the export of essential goods, but these have since been lifted. Third, countries have attempted to compensate for logistical and border transit issues caused by special sanitary requirements by expanding infrastructure; and simplifying and digitizing procedures on both road and rail. Fourth, all NCA countries have created online outreach portals and attempted to digitize various government services. However, their success varies greatly depending on the existing state of their paperless trade systems and infrastructure. Trade digitalization can support social distancing, while increasing trade efficiency, and inform businesses (especially SMEs) on the rapidly evolving regulatory environment under COVID-19. It is therefore recommended for countries to accelerate trade digitalization efforts, including by joining the Framework Agreement on Facilitation of Cross-border Paperless Trade in Asia and the Pacific.
Keywords: F13; F55; I18; 330; Trade Facilitation; COVID-19; North and Central Asia; Customs; Paperless Trade; Policy; Digital Trade; Trade digitalization